'A daddy is the same as a mummy': Swedish children in lesbian households talk about fathers and donors. (February 2014) - Malmquist, Anna; Möllerstrand, Anna; Wikström, Maria; Zetterqvist Nelson, Karin
The present article discusses how 12 children (five to eight years) in planned lesbian families talk about families, parents and specifically 'daddies' as such and not having a father themselves. Findings from child interviews demonstrate that the children described daddies as 'the same' as mummies, i.e. as having the same functions. This contrasts with previous research showing how children of heterosexuals often describe mothers and fathers as different. The children varied in terms of how they labelled donors. Some children adopted the denomination 'daddy', drawing on a paternity discourse, while others simply referred to him as 'a man'.